-2(2v-3)+7v=9+3(5v-2)

Simple and best practice solution for -2(2v-3)+7v=9+3(5v-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2v-3)+7v=9+3(5v-2) equation:


Simplifying
-2(2v + -3) + 7v = 9 + 3(5v + -2)

Reorder the terms:
-2(-3 + 2v) + 7v = 9 + 3(5v + -2)
(-3 * -2 + 2v * -2) + 7v = 9 + 3(5v + -2)
(6 + -4v) + 7v = 9 + 3(5v + -2)

Combine like terms: -4v + 7v = 3v
6 + 3v = 9 + 3(5v + -2)

Reorder the terms:
6 + 3v = 9 + 3(-2 + 5v)
6 + 3v = 9 + (-2 * 3 + 5v * 3)
6 + 3v = 9 + (-6 + 15v)

Combine like terms: 9 + -6 = 3
6 + 3v = 3 + 15v

Solving
6 + 3v = 3 + 15v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-15v' to each side of the equation.
6 + 3v + -15v = 3 + 15v + -15v

Combine like terms: 3v + -15v = -12v
6 + -12v = 3 + 15v + -15v

Combine like terms: 15v + -15v = 0
6 + -12v = 3 + 0
6 + -12v = 3

Add '-6' to each side of the equation.
6 + -6 + -12v = 3 + -6

Combine like terms: 6 + -6 = 0
0 + -12v = 3 + -6
-12v = 3 + -6

Combine like terms: 3 + -6 = -3
-12v = -3

Divide each side by '-12'.
v = 0.25

Simplifying
v = 0.25

See similar equations:

| 65*65-81*x*x=36*x*x | | -4/3w=24 | | 12-5/8 | | 3(-x+4)+6=-6x+3 | | 4/x-2=(-4/x+2)+(24/(x-2)(x+2)) | | 14m=400.40 | | 2n+7=5x | | 3v=3.75 | | 2(3x-5)=.5 | | 31.25=x/5 | | -2(x+2)=2x-1+5(2x+1) | | (7-x)(10-x)=(7)(10-1.5x) | | 6/10x=60 | | w/12.8=4 | | .40x+.15(140-x)=.19(140) | | -2(v+9)=7v+45 | | 6i+10y=-13 | | 2x-13=-7(x+7) | | 8x+4=-6+7x | | 3v=9/2 | | .25x+.15(140-x)=.19(140) | | y/4+3.2+5.2 | | 3v+6(v+2)=21 | | 13x=9x+12 | | 7(y-8)+2y=7 | | 30=6/5x | | -6u+3(u+7)=9 | | 3x-2-x=102 | | x(2x-5)+x(2x-2)=(4x+3)(x-2) | | .40x+.15(140-x)=.25(140) | | 2/3(4+3) | | 6x^4+5x^2-6=0 |

Equations solver categories